1983
DOI: 10.2337/diab.32.11.982
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Oxidation and Storage in Obese Non-insulin-dependent Diabetic Patients: Effects of Improving Glycemic Control

Abstract: We have determined total body carbohydrate and lipid oxidation rates in response to a standard breakfast in nine obese patients with non-insulin-dependent diabetes mellitus (NIDDM) and in seven age- and weight-matched controls. The patients with NIDDM were studied twice, once while in poor glycemic control (fasting blood glucose concentration 267 +/- 24 mg/dl, urinary glucose excretion 28.9 +/- 6.3 g/24 h) and again after modest glycemic improvement following 2 mo of fiber treatment (fasting blood glucose 227 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 12 publications
5
16
0
Order By: Relevance
“…The decrease in GRd of -3 mg/kg per min which occurred when FFA concentrations rose from -50 to -500 gM was accounted for equally by decreases in CHO oxidation and glycogen synthesis, while the decline in GRd which occurred when plasma FFA concentrations rose further (from -550 to -750 ,gM) was caused exclusively by a decrease in glycogen synthesis. These findings expanded earlier observations (13,43) that the effect of fat on CHO oxidation was relatively small and that the main problem in obese diabetic and nondiabetic subjects, whose FFA concentrations are commonly > 500 OM, was a defect in nonoxidative glucose disposal (1)(2)(3)(4)(5)(6)(7)(8)(9) and muscle biopsy samples revealed, however, that glycogen synthesis was already inhibited before inhibition of muscle GS activity. This indicated the presence of an additional, earlier fatty acid-induced block ofglycogen synthesis which was unrelated to an impairment of GS.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The decrease in GRd of -3 mg/kg per min which occurred when FFA concentrations rose from -50 to -500 gM was accounted for equally by decreases in CHO oxidation and glycogen synthesis, while the decline in GRd which occurred when plasma FFA concentrations rose further (from -550 to -750 ,gM) was caused exclusively by a decrease in glycogen synthesis. These findings expanded earlier observations (13,43) that the effect of fat on CHO oxidation was relatively small and that the main problem in obese diabetic and nondiabetic subjects, whose FFA concentrations are commonly > 500 OM, was a defect in nonoxidative glucose disposal (1)(2)(3)(4)(5)(6)(7)(8)(9) and muscle biopsy samples revealed, however, that glycogen synthesis was already inhibited before inhibition of muscle GS activity. This indicated the presence of an additional, earlier fatty acid-induced block ofglycogen synthesis which was unrelated to an impairment of GS.…”
Section: Discussionsupporting
confidence: 73%
“…While its cause remains uncertain, insulin resistance is known to be commonly associated with an inability of insulin to normally promote nonoxidative glucose disposal (glucose storage) and to activate skeletal muscle glycogen synthase (GS) (2)(3)(4)(5)(6)(7)(8)(9). There is evidence to suggest that in many instances the defects in glucose uptake and storage may be related to abnormal fat metabolism (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The data of the present and previous studies (16,17,(53)(54)(55) indicate that 30-40% ofan oral glucose load is immediately oxidized; specifically, in the present studies 24.9 g (37%) of a 67.6-g oral load was oxidized. About 35% of this (8.9 g) could be accounted for by muscle.…”
Section: Discussionsupporting
confidence: 55%
“…Thereafter, a number of studies have confirmed that elevated rates oflipid oxidation are associated with impaired oxidative glucose disposal in nondiabetic and NIDD subjects (18)(19)(20)(21)(22)(23)(24). However, it remains unproven whether enhanced lipid oxidation also inhibits the nonoxidative pathways of glucose metabolism (21)(22)(23)(24)(25)(26). An association between elevated plasma FFA/lipid oxidation and excessive rates of hepatic glucose production (HGP) has also been suggested (4,12,19,27).…”
Section: Introductionmentioning
confidence: 99%